Development of restaurant service sabotage scale - Tao, Chen-Wei (Kansas State University, 2017)
Service sabotage refers to employees' deliberate actions that negatively affect service, functional quality, employee-customer rapport, and company performance. Almost all frontline employees in the hospitality industry have witnessed service sabotage behaviors, and 85% admitted to engaging in such misbehaviors. Despite the prevalence and profound impact of service sabotage, it has been a challenge for researchers to measure the construct and understand specific and contextualized restaurant service sabotage behaviors. Thus, the purpose of this dissertation was to develop a reliable and valid scale to measure restaurant service sabotage. A mixed methods research design was applied. A qualitative study was conducted to explore prevalent restaurant service sabotage behaviors and to generate an item pool for the initial scale, followed by two quantitative studies with two different groups of non-managerial frontline employees in full-service restaurants to refine and validate the scale. Guided by critical incident technique, 243 critical incidents were derived from the in-depth interviews (n = 26). Of those, 28 explicit types of restaurant service sabotage behaviors were identified and further categorized into three behavioral groups: targeting customers, colleagues, and restaurants. In conjunction with scale items extracted from related measures, an initial instrument consisting of 39 items was developed and administered to an online restaurant employee panel by hiring a professional research firm. A total of 419 usable responses were collected and analyzed using principal axis factoring with a promax rotation. Results revealed a 13-item scale with three dominant factors. To validate the scale, 463 usable responses were gathered for data analyses. Results of the confirmatory factor analyses indicated a good model fit of the three-factor model, Chi-square/df=3.15, GFI=.96, CFI=.97, NFI=.95, and RMSEA=.07 while reducing the scale items from 13 to 10 and supporting the scale's dimensionality. Tests for validating construct validity were all fully supported. Cronbach’s alpha coefficients were all greater than .70, showing internal consistency of the scale. This psychometrically valid and conceptually sound scale may be applied in future restaurant service sabotage research and may stimulate additional studies to advance the theory and explore the criterion network. Implications, limitations, and direction for future research are discussed.
Keywords: Scale development; Scale refinement; Scale validation; Frontline employeeRestaurant service sabotage